Homologous recombination-DNA damage response defects increase TMB and neoantigen load, but not effector T cell density and clonal diversity in pancreatic cancer - Mengyue Lei; Jessica Gai; Thomas J. McPhaul; Huijuan Luo; Penghui Lin; Dongbing Liu; Michael Pishvaian; Nicholas J. Roberts; Kui Wu; Jin He; Lei Zheng (Experimental Hematology & Oncology)
Abstract Pancreatic ductal adenocarcinoma (PDAC) is highly resistant to chemotherapy. However, PDAC with germline BRCA mutations, which lead to homologous recombination (HR) deficiency (HRD), demonstrated an increased sensitivity to platinum-based chemotherapy regimens. This increased chemosensitivity was also seen in PDACs with germline or somatic mutations in the DNA double-strand damage response (DDR) genes beyond canonical HR genes such as BRCA1, BRCA2, and PALB2. However, there are no consensus methods to determine HRD status; and neither is there a well-defined list of HR-DDR genes. In addition, how HRD and/or HR-DDR gene mutation status impacts the tumor immune microenvironment including tumor mutation burden (TMB), neoantigen load, T cell receptor (TCR) repertoire, and effector T cell infiltration is unknown. Thus, in this study, we developed a new method to categorize PDACs into HRD-positive and HRD-negative subgroups by using results from whole exome sequencing, whole genome sequencing, or both into consideration. We classified a cohort of 89 PDACs into HRD-positive (n = 18) and HRD-negative (n = 69) tumors. HR-DDR gene variants were identified more frequently in HRD-positive PDACs than HRD-negative PDACs, with RAD51B, BRCA2 and ATM alterations most frequently identified in HRD-positive PDACs. Notably, TMB and neoantigen load was significantly higher in HRD-positive PDACs compared to HRD-negative tumors. Interestingly, HRD-positive PDACs, PDACs with high tumor mutational burden, and PDAC with high neoantigen load were all associated with lower CD8 + T lymphocyte infiltration and T cell clonal diversity, suggesting a mechanism of resistance to immune checkpoint inhibitors (ICIs). Therefore, this study suggests that treatments to enhance effector T cell infiltration and T cell clonal diversity may overcome resistance to ICI-based immunotherapy in HRD-positive PDACs.